THE THOUGHT OF EDUCATION REFORMATION OF NGUYEN TRUONG TO AND ITS SIGNIFICANCEIN EDUCATION RENOVATION IN VIETNAM TODAY - Thu Hien, Bui Thi (International Journal of Psychosocial Rehabilitation, 2024)
Nguyen Truong To was one of the initiations of the country’s reform trend in Vietnam in the late nineteenth century. His systematic and comprehensive reform proposals cover all areas of social life; in it, he paid much attention to education reform. His reform ideas reflect a new vision and thinking to meet the requirements of national history, protection of sovereignty and national development. The article clarifies the content of educational reform ideology of Nguyen Truong To, from which we draw some implications for the cause of educational innovation in Vietnam nowadays.